Liver cirrhosis is a risk-factor for Pneumocystis jirovecii associated mortality - Peschel, Georg; Happ, Nils; Bornschein, Jan; Weis, Florian; Schmid, Stephan; Mueller, Martina; Selgrad, Michael (Frontiers in Medicine, 2024)
Pneumocystis jirovecci (PCJ) infection pneumonia (PCP) is a life threating disease in immunodeficient patients.Liver cirrhosis itself can lead to immunodefiency, however little is known if Pneumocystis jirovecci PCJ infection affects the outcome of patients with liver cirrhosis.We aimed to assess the predictors for Pneumocystis jirovecci PCJ-associated mortality in patients with Pneumocystis jirovecciPCJ infection treated at intensive care units.A total of 151 patients hospitalized between January 2013 and November 2019 with a PCR-confirmed Pneumocystis jirovecci infection were retrospectively included in this study and analysed for clinical predictors for PCJ associated mortality .The overall mortality in our patient cohort was 60%. Out of 151 patients included in the analysis, 67 (44%) patients suffered from liver cirrhosis. Patients with an advanced liver cirrhosis (Child-Pugh Stadium class C) showed the highest mortality rate of 84.7%. The presence of a liver cirrhosis was associated with a significant increased risk of mortality (OR: 4.809) [95%-CI: 2.32-9.97]; p < 0.001). There was a significant correlation of Meld score and mortality (r=0.612, p < 0.001).To our knowledge, this study represents the largest evaluation of Pneumocystis jirovecci PCJ infection in patients with advanced liver cirrhosis. Cirrhosis associated immune dysfunction (CAID) describes the spectrum of immunological disturbances in patients with cirrhosis, which is linked to a heightened vulnerability to bacterial infections. Our data indicate a heightened susceptibility to viral ifungal infections. Understanding the phenotypic manifestations of CAID could lead to immune-targeted therapies aimed at reducing infection susceptibility and decreasing CAID-associated mortality in cirrhosis patients.